The Appeal of Stock Investment for Future Profit Generation with Minimal Capital - Hattie Berhadru Kerthi (Akademi Sertifikasi Profesi Internasional, 2025)
This service addresses the misconception that stock investment necessitates substantial cash and is inherently risky, despite the fact that fractional stock innovation has removed these financial hurdles. The primary issue encountered is the inadequate comprehension of basic fundamental analysis, leading to apprehension about investing and susceptibility to trends devoid of a robust base. The objective of this program is to enhance stock investment literacy, particularly the participants' capacity to analyze blue-chip stocks through fundamental ratios (PER and PBV), and to promote initial investments with minimal cash. This service's innovation is the Stock Micro-Investment Module (MIS), which emphasizes long-term investment (buy and hold) methods rather than day trading. The findings indicated a 45% rise in the average fundamental analytical literacy score among participants, with 80% successfully executing their initial fractional share purchase from a blue-chip issuer, thereby establishing a secure and quantifiable avenue for stock ownership